2021
DOI: 10.3126/janr.v4i2.33915
|View full text |Cite
|
Sign up to set email alerts
|

Shisham (Dalbergia sissoo) decline by dieback disease, root pathogens and their management: a review

Abstract: Shisham or sissoo (Dalbergia sissoo) is an important multipurpose tree with great economic importance, but this tree has been infected by various root pathogens. This review article shows the works conducted on root pathogens and die back disease of Shisham and their management. Around seventy-one endophytic fungus has been found in sissoo trees in Nepal. Several fungi, including, Fusarium solani, F. oxysporum, Ganoderma lucidum, Phellinus gilvus, Polypours gilvus, Rhizoctonia solani, Polyporus spongiosum, etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Trichoderma species are reported as the most potent biocontrol agents against G. lucidum due to their ability to retard its growth by competing for space, nutrients, mycoparasitism stimulating plant growth and initiating plant defense mechanism [91][92][93][94][95][96]. However, Trichoderma species has been observed to provide protection to plants only during the initial stages of the disease and have no effect on highly infected trees [97] In a study, out of three Trichoderma species viz; T. psuedokoningii, T. harzianum, and T. viride, the most significant control of radial growth of G. lucidum was shown by T. harzianum (68.5%) [84]. Biocontrol agents such as T. harzianum, Gliocadium viride, T. viride, Bacillus, and Pseudomonas, and so forth have been reported effective against pathogenic Ganoderma species [41, [98][99][100].…”
Section: Biocontrol Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichoderma species are reported as the most potent biocontrol agents against G. lucidum due to their ability to retard its growth by competing for space, nutrients, mycoparasitism stimulating plant growth and initiating plant defense mechanism [91][92][93][94][95][96]. However, Trichoderma species has been observed to provide protection to plants only during the initial stages of the disease and have no effect on highly infected trees [97] In a study, out of three Trichoderma species viz; T. psuedokoningii, T. harzianum, and T. viride, the most significant control of radial growth of G. lucidum was shown by T. harzianum (68.5%) [84]. Biocontrol agents such as T. harzianum, Gliocadium viride, T. viride, Bacillus, and Pseudomonas, and so forth have been reported effective against pathogenic Ganoderma species [41, [98][99][100].…”
Section: Biocontrol Methodsmentioning
confidence: 99%
“…In case of D. sissoo root rot caused by G. lucidum , it has been observed that monoculture reforestation in areas of previous infection has led to enhanced mortality of trees [9]. Incidences of Ganoderma root rot can be lowered by removing the stumps and residual roots of infected trees as they serve as the source of disease spread [84]. For ensuring disease free stock of plants irregular and close planting, flooded irrigation of, repeated plowing, and so forth should not be followed [85].…”
Section: Management Of G Lucidum Infestationmentioning
confidence: 99%
“…The disease exhibited a clustered spread pattern, with some random and uniform patterns observed in specific plant groups and locations [ 487 ]. Ganoderma lucidum is a particularly significant pathogen associated with the large-scale death of Shisham trees by root rot ( Dalbergia sissoo ) [ 488 ]. UGM’s arboretum in Yogyakarta has experienced tree decline and death from Ganoderma sp.…”
Section: Research On Butt Rot and Root Rot Diseases Of Important Pere...mentioning
confidence: 99%
“…Dieback disease caused up to 55% mortality of the shisham population in various regions of subcontinent and caused up to 55% mortality of the shisham population in different regions of subcontinent (Shah et al 2021). In Pakistan, Dalbergia sissoo 5% mortality occurred through 1990 -1991, 43% in 2001 and 25% during 1999 -2000 in different districts of Punjab province (Gill et al 2001).…”
Section: Introductionmentioning
confidence: 99%